New insights into an X-traordinary viral protein - Schaller, Torsten; Bauby, Hélène; Hué, Stéphane; Malim, Michael H.; Goujon, Caroline (Frontiers in Microbiology, 2014)
Vpx is a protein encoded by members of the HIV-2/SIVsmm and SIVrcm/SIVmnd-2 lineages of primate lentiviruses, and which is packaged into viral particles. Vpx plays a critical role during the early steps of the viral life cycle and has been shown to counteract the SAMHD1 restriction factor in myeloid and resting T cells. However, it is becoming evident that Vpx is a multifunctional protein in that SAMHD1 antagonism is not its sole role. This review summarises the current knowledge on this X-traordinary protein.